Pelatihan Peningkatan Kompetensi Riset, Penulisan, Dan Publikasi Untuk Komunitas Aksi Penggerak (KORA-KORA) Di Provinsi Maluku - Misbah Fikrianto; La Mansur; Alfi Hasan (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Improving teacher competency is essential for enhancing the overall quality of education. Teachers play a strategic role in implementing effective learning processes. To support this, a training program was held from October 5th to 7th, 2024, at the Manise Hotel, Ambon City, Maluku Province. The training aimed to develop research, writing, and publication skills among teachers and educational personnel. The event was attended by 50 participants, including two education personnel and members of the Maluku Province Teacher Mobilization Team. The instructors for this training were Mr. La Mansur, Mr. Deni Hadiana, Mr. Misbah Fikrianto, Mrs. Rini Anita Putri, and Mr. Alfi Hasan. This initiative was supported by the Maluku Provincial Teacher Mobilization Centre, which mobilized the Mobilizing Action Community (KORA-KORA), known for its strong commitment to improving educational services, strengthening quality, and implementing various programs. The training used a combination of methods, including lectures, group discussions, collaborative learning, and project development. The goal was to make research enjoyable, encourage creative writing, and support participants in publishing their work. According to post-training observations, around 95% of the participants expressed satisfaction with the training and felt it was appropriate for their needs. Participants also hoped that similar activities would continue in the future. This continuous development of competencies ensures that teachers and educational personnel can sustain improvements in their professional capabilities.